Interaction Kinetics of Oximes with Native, Phosphylated and Aged Human Acetylcholinesterase - Radić, Zoran (2010)
Oximes are commonly used nucleophilic reactivators of alkyl phosphorylated and alkyl methylphosphonylated acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE). Covalent inhibition of these enzymes by organophosphate (OP) pesticides results typically in phosphorylated enzymes, while covalent inhibition by nerve agent OPs results in methyl phosphonylated cholinesterases. In this study we determined kinetic constants for interaction of three triazole containing oximes with native human AChE, enzyme diethylphosphorylated by paraoxon, enzyme phosphonylated by VX and cyclosarin as well as enzyme aged upon phosphonylation by soman. Stopped-flow kinetics of oxime interaction was monitored using quenching of intrinsic tryptophan fluorescence of AChE as an indicator of oxime binding. Triazole oximes were efficiently synthesized using copper catalyzed cycloaddition between azide and alkyne building blocks (“Click chemistry”). Equilibrium dissociation constants determined for both native enzymes were in low micromolar range for all three oximes, while dissociation constants for phosphylated (phosphorylated and phosphonylated) enzymes were typically one to two orders of magnitude larger. Dissociation constants for interaction with aged enzymes were similar or smaller than those determined for native enzymes. Similar results were obtained with reference oximes, 2PAM and HI6. Association rate constants for formation of oxime complexes were similar for both native, phosphylated and aged enzymes. In summary our data suggest that modification of active site gorge in AChEs by phosphylation of the active serine compromises oxime binding. Dealkylation of phosphonylated enzyme, however opens space in the gorge allowing oximes to bind tighter.